Marine debris is a living environmental problem that is now a global issue that attracts everyone's attention as it threatens marine ecosystems. The shipment of garbage from the State district crossing the Kaliakah and Ijogading rivers contributed to the scale of the waste distribution on the coast. The study aims to analyze the concentrations (quantity and weight), characteristics (type, weight, size and shape) and distribution of garbage stranded in the coastal areas of Banyubiru Village, Balu - Ansisko Simbolon (Program Studi Ilmu Kelautan, FIPAK, Universitas OSO, 2024)
Marine debris is a living environmental problem that is now a global issue that attracts everyone's attention as it threatens marine ecosystems. The shipment of garbage from the State district crossing the Kaliakah and Ijogading rivers contributed to the scale of the waste distribution on the coast. The study aims to analyze the concentrations (quantity and weight), characteristics (type, weight, size and shape) and distribution of garbage stranded in the coastal areas of Banyubiru Village, Baluk and Cupel. The waste data collection method adopts the method developed by the Commonwealth Scientific and Industrial Research Organization (CSIRO) Global Plastic Pollution Project by naming the transec line vertically to the coastline three times. Deposits in the coastal areas of Banyubiru Village, Baluk and Cupel are scattered across the area with concentration values of marine garbage ranging from 1.20 to 6.71 items/m2 with an average of 2.74 items/m2 and the resulting concentration of massive marine waste ranges from 13.50 to 93.05 grams/m2, with average of 49.416 grams/m2. Based on the amount of garbage it is classified by the soft plastic class 30%, while weight it is dominated by the wood class 23%. The total weight of all types of marine waste is 37.370 grams. The size of trash is 16-21 cm2 29%. 46% of the waste in the coastal area is whole and 54% is fragmented. In general, coastal marine debris is mostly consumer products. Therefore, public awareness plays an important role in reducing the amount of garbage in the region.